Fiscal Rules Introduction: An overview and selected open issues - Kešeljević, Kešeljević; Aristovnik, Aleksander (Naše gospodarstvo/Our economy, 2013)
Fiscal rule can be defined as a permanent restriction for fiscal policy, specified by an indicator of fiscal spending. Fiscal rules vary greatly in terms of their respecti- ve forms. Therefore, the key purpose of this paper is to provide an in-depth account of the problems and dilemmas appearing upon the introduction of different fis- cal rules. The five most common forms of fiscal rules are analyzed from the aspect of fiscal consolidation and economic stabilization. The authors describe the requirements for greater effectiveness of fiscal rules and discuss the reasons against their implementation. The final chapter includes a political-economic analysis of the tra- de-off between government credibility and flexibility in the fiscal policy, a review of different institutional frameworks, penalties and exemptions, and a reflection on what time can be deemed (un)suitable for introducing a fiscal rule.
Keywords: fiscal rules; fiscal policy; OECD; MDS